A Black-Scholes option pricing model with transaction costs - Amster, P. (2005)
We consider a boundary value problem for a nonlinear differential equation which arises in an option pricing model with transaction costs. We apply the method of upper and lower solutions in order to obtain solutions for the stationary problem. Moreover, we give conditions for the existence of solutions of the general evolution equation. © 2004 Elsevier Inc. All rights reserved.